Cobalt‐Sputtered Anodic Aluminum Oxide Membrane for Efficient Photothermal CO2 Hydrogenation. Issue 9 (10th June 2021) - Lou, Deyue; Xu, Ao‐Bo; Fang, Yaosi; Cai, Mujin; Lv, Kangxiao; Zhang, Dake; Wang, Xiao; Huang, Yang; Li, Chaoran; He, Le
Abstract: The rational design of nanoarray‐structured catalysts is an accessible way to increase light absorption ability and boost photothermal CO2 conversion efficiency. However, practical application of current nanoarrays is hindered by complex synthesis procedures, high costs, and low catalyst yields. Herein, we report a simple, robust method to prepare efficient photothermal catalyst by sputtering Co nanoparticles on commercial anodic aluminum oxide (AAO) membrane. The detailed study shows that gas diffusion and catalytic activity can be affected by AAO structures, such as channel size and shape. The optimized Co@dpAAO catalyst reached a record Co‐based photothermal CO2 conversion rate of 1666 mmol ⋅ gCo −1 ⋅ h −1 . This study not only provides a facile way to synthesize efficient catalysts, but also promotes the understanding of constructing nanoarray‐based photothermal catalysts. Abstract : Simply by sputtering Co nanoparticles on commercial anodic aluminum oxide (AAO) membranes, highly efficient photothermal catalyst for CO2 hydrogenation can be obtained. The dual‐pass AAO with larger channel size can facilitate gas diffusion and thus boost CO2 conversion rates to the highest value among the reported Co photothermal catalysts.